Analisis Penataan dan Penyimpanan Arsip Inaktif untuk Memudahkan Temu Kembali di Record Center Balai Pemberdayaan Industri Persepatuan Indonesia - Moh. Yuski Anwar; Tatiana Kristianingsih (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The Indonesian Footwear Industry Empowerment Agency (BPIPI) generates inactive records managed by a records center. The management of inactive records at the records center particularly the organization process still faces challenges that hinder the retrieval process. However, well-organized inactive records can enhance the effectiveness of storage and facilitate record retrieval. This study aims to describe and analyze the implementation of the organization, storage, and retrieval of inactive records at BPIPI. This study employs a qualitative descriptive approach, with the research subjects being First-Class Archivists and Skilled Archivists at BPIPI. Data were collected through observation, interviews, and documentation, with the research focus on the organization, storage, and retrieval of inactive records. The data obtained were then analyzed using the Miles and Huberman method, which consists of data collection, data reduction, data presentation, and drawing conclusions and verification. The research findings indicate that the organization and storage of inactive records at BPIPI have been carried out in accordance with Sukma & Fajer’s theory, from the examination of records, the organization of records into boxes, the numbering of boxes, to the storage of boxes on archive shelves. However, during the box numbering stage, there were still challenges related to discrepancies between the information on the labels and the contents of the boxes. The record retrieval process has also been carried out in accordance with Dewi’s theory through the verification of record codes, the search for and retrieval of records using a loan slip, and the handover of records to users. However, the accuracy rate remains at 1.47%, which indicates that the organization and storage of records need to be reviewed. In general, the organization and storage of inactive records at BPIPI have been carried out effectively, although there are still challenges, namely discrepancies between the information listed on the archive box labels and the actual contents of the boxes. This study is limited to a single agency and focuses solely on inactive paper-based records. Further research is recommended to examine the implementation of a digital records management system.